2016
DOI: 10.1007/978-3-319-46100-7_5
|View full text |Cite
|
Sign up to set email alerts
|

Two Experimental Virtual Paradigms for Stress Research: Developing Avatar-Based Approaches for Interpersonal and Evaluative Stressors

Abstract: In light of the rather limited ecological validity of paradigms traditionally used for social stress research, the current paper set out to introduce virtual analogues of the Cyberball-Game (Williams, 2007) and the Trier Social Stress Test (Kirschbaum, Pirke, & Hellhammer, 1993). Both were tested in samples of healthy adults using salivary cortisol, self-reported stress and presence as dependent measures. Results indicate a significant rise in cortisol levels and subjective stress; presence, however, was not c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
0
7
0
1
Order By: Relevance
“…Virtual environment-based Cyberball paradigms have emerged, that place the participant into a virtual environment with interactive virtual humans [128,143,144,145,146]. Findings from these studies reveal that the more immersive virtual environments induced greater feelings of ostracism in participants.…”
Section: Virtual Induction Of Social Painmentioning
confidence: 99%
See 4 more Smart Citations
“…Virtual environment-based Cyberball paradigms have emerged, that place the participant into a virtual environment with interactive virtual humans [128,143,144,145,146]. Findings from these studies reveal that the more immersive virtual environments induced greater feelings of ostracism in participants.…”
Section: Virtual Induction Of Social Painmentioning
confidence: 99%
“…An alternative approach using a virtual reality-based TSST has emerged in a number of studies [ 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 ]. Studies using a virtual reality-based TSST have found significant stress reactions, with peripheral physiological reactions and self-reported stress elevations comparable to those in response to the in vivo TSST.…”
Section: Virtual Induction Of Social Stressmentioning
confidence: 99%
See 3 more Smart Citations